Monitoring Penutupan Lahan di DAS Grindulu dengan Metode Penginderaan Jauh dan Sistem Informasi Geografis - Beny Harjadi (Universitas Muhammadiyah Surakarta, 2010)
Catchments area can be analyzed as management system. Catchments area acquire input and it processed by the system to produce output. Land covers in catchments area are closely related to land use pattern and to management system. Land use changes to building area, agriculture and another activity are related to anthropological characters effected by change in function from vegetated land to unvegetated land. This condition have negative influences to the condition of carchment area. The damaged level of catchment area can be reflected by flood susceptibility, droughness, erosion and sedimentation, related impact onsite and offsite, so it is need a comprehensive management system from up land to low land river. To give information of land use in catchments area it needs accurate data about land cover in wide range. Remote sensing and Geographic Information System (GIS) are applicable to monitor land coverage of management catchments area. The aim of this paper is to analyze land cover using remote sensing and GIS to catchments area monitoring and evaluation. Land use in watershed connection with the pattern of nature resources by the community and the management of watershed. Total area of land use Grindulu watershed was 65.539 ha. From the map of land use could be seen that the spreading of the equitable meeting forest from the upstream to lower, and most property of the people. Land use became 8 classes, that is: Agroforestry (20%), Open Land (12%), Rare Forest (1%), Dense Forest (29%), Village (34%), Paddy (0.4%), River (0.2%), and Field (3%).